Theoretical Substituent Electrophilicities - Caroli-Rezende, M (2011)
Hammett-like equation, relating theoretical global and substituent electrophilicities, is derived for substituted ethylenes and benzoic acids, allowing the calculation of electrophilic substituent constants ??. Correlations are given between the theoretical ?? constants and kinetic or thermodynamic parameters of various chemical processes from the literature. Though electrophilic substituent constants are formally similar to the Hammett constants, they are derived from entirely different theoretical postulates. The similarities and differences between the two sets of constants are discussed and rationalized in terms of the definition of the electrophilic power of a chemical species. © 2011 Sociedade Brasileira de Química.